INSTRUMENTAL NEUTRON ACTIVATION ANALYSIS OF CONCENTRATIONS OF VANADIUM, MANGANESE, ARSENIC, MERCURY, CADMIUM AND ALUMINIUM IN MUSCLE TISSUES OF FOUR FISH SPECIES FROM THE WEIJA LAKE IN GHANA - Edmund Ameko; Sylvester Achio; Jonathan Okai – Armah; Samuel Afful (European Scientific Journal, ESJ, 2014)
The Weija Lake, formed from the Densu River, presently one of the most polluted rivers in Ghana, is a domestic source of Tilapia and Catfish. This study determined the concentration of V, Mn, As, Hg, Cd, and Al in the muscles of Tilapia zillii, Clarias gariepinus, Sarotherodon galilea, and Oreochromis niloticus from the Weija Lake using Instrumental Neutron Activation Analysis. The relationships between metal concentrations in fish muscles on one hand, and fish length and weight, condition factor (Kf), and metal concentrations in the water on the other hand were also determined. All four fish species showed negative allometric growth. Kf correlated negatively with V, Mn and Al concentrations in T. zilli, and positively with V, Mn and Al concentrations in C. gariepinus, O. niloticus and S. galilea. Fish lengths and weights correlated negatively with V, Mn and Al concentrations in fish, with no significant correlation with As, Hg and Cd levels. Metal concentrations in water correlated positively with concentrations in fish. The Estimated Average Daily Doses from consumption of fish from the lake were 6113μg - 33778.5μg V, 114,098.2μg - 530,371μg Al, and 34,383.6μg - 129492μg Mn respectively, and these exceeded the recommended ADIs of <1800μg V, 142.8μg Al, and 11,000μg Mn respectively. The results indicate safe levels of Arsenic, Mercury, and Cadmium, and unsafe levels of Vanadium, Aluminium and Manganese in T. zillii, C. gariepinus, S. galilea, and O. niloticus from the lake.